Quantitative and qualitative optimization of allergen extraction from peanut and selected tree nuts. Part 2. Optimization of buffer and ionic strength using a full factorial experimental design. (1st March 2016) - L'Hocine, Lamia; Pitre, Mélanie
Highlights: Buffer type and ionic strength affected protein profile, abundance, and IgE-binding. Buffer type and ionic strength can be manipulated for selective allergen solubility. Non optimal extraction protocol may lead to failure to detect important allergens. Optimal buffer system conditions are suggested for peanut, almond, hazelnut, and pistachio. Abstract: A full factorial design was used to assess the single and interactive effects of three non-denaturing aqueous (phosphate, borate, and carbonate) buffers at various ionic strengths ( I ) on allergen extractability from and immunoglobulin E (IgE) immunoreactivity of peanut, almond, hazelnut, and pistachio. The results indicated that the type and ionic strength of the buffer had different effects on protein recovery from the nuts under study. Substantial differences in protein profiles, abundance, and IgE-binding intensity with different combinations of pH and ionic strength were found. A significant interaction between pH and ionic strength was observed for pistachio and almond. The optimal buffer system conditions, which maximized the IgE-binding efficiency of allergens and provided satisfactory to superior protein recovery yield and profiles, were carbonate buffer at an ionic strength of I  = 0.075 for peanut, carbonate buffer at I  = 0.15 for almond, phosphate buffer at I  = 0.5 for hazelnut, and borate at I  = 0.15 for pistachio. The buffer type and its ionic strength could be manipulated to achieve the selective solubility of desired allergens.